Pengaruh Kepemimpinan Autentik Terhadap Work Engagement Melalui Psychological Capital Sebagai Variabel Intervening (Studi Pada Karyawan Bagian Kantor PT. Perkebunan Nusantara X Pabrik Gula Lestari Di Nganjuk) - APRILIA FIRDAUS, BELLA (Jurnal Ilmu Manajemen (JIM), 2018)
Abstract PT. Perkebunan Nusantara X Pabrik Gula Lestari is a company engaged in sugar-producing industries as one of the basic needs of Indonesian society. In an effort to achieve the vision and mission set by the company then the employees at PT. Perkebunan Nusantara X Pabrik Gula Lestari must have high work engagement. In an effort to improve employee work engagement of course needed support from other factors such as authentic leadership style and employee psychological capital. Leader of PT. Perkebunan Nusantara X Pabrik Gula Lestari has implemented an authentic leadership style. The purpose of this study was to examine and analyze the effect of authentic leadership on psychological capital. Effect of authentic leadership influence and psychological capital on work engagement, as well as authentic leadership influence on work engagement through psychological capital. The sample used in this study amounted to 57 employees of office. Perkebunan Nusantara X Pabrik Gula Lestari. The data analysis technique used software SmartPLS. The results of this study indicate that authentic leadership has a significant positive effect on psychological capital, authentic leadership has a significant positive effect on work engagement, psychological capital have a significant positive effect on work engagemet and psychological capital able to mediate the influence of authentic leadership towards work engagement. Keywords: Authentic Leadership, Work Engagement, Psychological Capital